2013
DOI: 10.1590/0004-282x20130027
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue oxidative damage as a possible mechanism for the deleterious effect of a chronic high dose of estradiol on learning and memory in ovariectomized rats

Abstract: In addition to antioxidative effects, estrogens also exert pro-oxidative actions. The effect of chronic administration of a high dose of estradiol valerate on Morris water maze tasks and brain tissues oxidative damage was investigated. The Sham-Est and OVX-Est groups were treated with estradiol valerate (4 mg/kg) for 12 weeks. Escape latency and traveled path in the Sham-Est and OVX-Est groups were significantly higher than in the Sham and OVX groups (p<0.01 and p<0.001). In the probe trial, the animals of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Ovarian hormones not only play an important role in reproductive behavior, but also involve in emotion, memory, neuronal survival and perception of somatosensory stimuli 3,11 . On the other hand, mood disorders in women have been reported to be more common than men 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian hormones not only play an important role in reproductive behavior, but also involve in emotion, memory, neuronal survival and perception of somatosensory stimuli 3,11 . On the other hand, mood disorders in women have been reported to be more common than men 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides of genetic, social, environmental and nutritional factors, it is suggested that sex hormones may have important roles in the pathogenesis of anxiety 2 . Interestingly, it is suggested that estrogen has protective roles against depressive disorders, Alzheimer's disease, Parkinson's and anxiety 3,4 . Similar to antidepressant drugs, estrogens are also known to increase the amounts of noradrenaline and serotonin in the CNS which may have role for regulating the mood and decreasing the susceptibility to depression 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance was read at 535 nm. The MDA concentration was calculated according to follow equation 18 . C (M) = Absorbance / 1.56 × 10 Determination of total thiol contents DTNB (2, 2'-dinitro-5, 5'-dithiodibenzoic acid) reagent which reacts with the SH group, was used to determine the total thiol contents.…”
Section: Mda Assessmentmentioning
confidence: 99%
“…The absorbance of DTNB reagent was also read as a blank (B). Total thiol concentration (mM) was calculated as follow equation 18 . Total thiol concentration (mM) = (A2 -A1 -B) × 1.07 / 0.05 × 13.6…”
Section: Mda Assessmentmentioning
confidence: 99%
“…Learning and memory in ovariectomized rats appears to be affecting by administration of high exogenous levels of estradiol (4mg/kg BW), due to enhance oxidative stress [19]. Estrogen therapy (weekly injections of estradiol valerate (2 mg/kg; i.m.)…”
Section: Discussionmentioning
confidence: 99%